(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Glucocorticoids have therapeutic benefits in the management of several inflammatory and immunological disorders. Despite these medicinal effects, they have the drawback of causing metabolic disorders such as hyperglycemia, insulin resistance etc., which is known to be a key indicator of metabolic syndrome. Metabolic syndrome is a major predisposing factor to type 2 diabetes mellitus and cardiomyopathy. This study was designed to compare and evaluate the effects of saxagliptin, metformin and intranasal insulin (when used singly or in combination) on dexamethasone induced insulin resistance. Fifty-six female rats were randomly assigned into eight groups. Group 1 represented the control; Group 2 was administered with dexamethasone (1mg/kg) (untreated); Group 3 received dexamethasone + intranasal insulin (2IU); Group 4 received dexamethasone + intranasal insulin + metformin (40mg/kg); Group 5; received dexamethasone + intranasal + saxagliptin (8mg/kg); Group 6 received dexamethasone + metformin (40mg/kg); Group 7 received dexamethasone + saxagliptin (8mg/kg); Group 8 received dexamethasone + saxagliptin(8mg/kg) + metformin(40mg/kg). Treatments were given for one week. At the end of the study, blood samples were collected for biochemical assays and pancreas excised for histological examination. Dexamethasone (1mg/kg) induced hyperglycemia, hyperinsulinemia, dyslipidemia, impaired glucose tolerance and disrupted the structural integrity of the pancreas. Treatment with saxagliptin, metformin and their combination significantly decreased blood glucose level, decreased LDL Level and improved glucose tolerance. The selected hypoglycemic agents used in present study ameliorate the dexamethasone induced hyperglycemia and insulin resistance of which the combination of metformin with saxagliptin showed greater efficacy.